2024
DOI: 10.1007/s10764-024-00415-9
|View full text |Cite
|
Sign up to set email alerts
|

Combinatoriality and Compositionality in Everyday Primate Skills

Nathalie Gontier

Abstract: Human language, hominin tool production modes, and multimodal communications systems of primates and other animals are currently well-studied for how they display compositionality or combinatoriality. In all cases, the former is defined as a kind of hierarchical nesting and the latter as a lack thereof. In this article, I extend research on combinatoriality and compositionality further to investigations of everyday primate skills. Daily locomotion modes as well as behaviors associated with subsistence practice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 133 publications
1
5
0
Order By: Relevance
“…Through analysing the curvature of composite models, we identified that these subroutines of actions were between 2-8 elements long (mean = 4.6 sequence elements, N = 5). Our results are therefore consistent with previous descriptions of how great apes organize sequences of actions during food processing behaviours, including those which involve the use of tools (Byrne et al, 2013; Byrne and Russon, 1998; Gontier, 2024). Apes are theorized to decompose goals into subgoals which are addressed through short, stereotyped subroutines of actions (Byrne et al, 2013; Byrne and Russon, 1998), thus, these models of behavioural organization are identical to the composite structuring model in our analysis.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Through analysing the curvature of composite models, we identified that these subroutines of actions were between 2-8 elements long (mean = 4.6 sequence elements, N = 5). Our results are therefore consistent with previous descriptions of how great apes organize sequences of actions during food processing behaviours, including those which involve the use of tools (Byrne et al, 2013; Byrne and Russon, 1998; Gontier, 2024). Apes are theorized to decompose goals into subgoals which are addressed through short, stereotyped subroutines of actions (Byrne et al, 2013; Byrne and Russon, 1998), thus, these models of behavioural organization are identical to the composite structuring model in our analysis.…”
Section: Discussionsupporting
confidence: 92%
“…These analyses should include sequential manual behaviours which vary in their technical complexity, and should include both complex, multi-stage manual behaviours (e.g. nest building and complex foraging tasks which do not require tools), as well as simpler feeding tasks which require fewer processing steps (Gontier, 2024).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations